Nocardia Beijingensis psoas abscess and subcutaneous Phaeohyphomycosis caused by Phaeoacremonium parasiticum in a renal transplant recipient: The first case report in Thailand - Nattawan Palavutitotai (2018)
© 2015, SEAMEO TROPMED Network. All rights reserved. We describe the first case of a psoas muscle abscess caused by Nocardia beijingensis and subcutaneous phaeohyphomycosis caused by Phaeoacremonium parasiticum in a renal transplant recipient. The patient was treated for nocardiosis with percutaneous drainage and intravenous trimethoprim/sulfamethoxazole (TMP/SMX) combined with imipenem for 2 weeks, followed by a 4-week course of intravenous TMP/SMX and then oral TMP/SMX. During hospitalization for the psoas muscle abscess the patient developed cellulitis with subcutaneous nodules of his right leg. Skin biopsy and cultures revealed a dematiaceous mold, subsequently identified as P. parasiticum by DNA sequencing. The subcutaneous phaeohyphomycosis was treated with surgical drainage and liposomal amphotericin B for 4 weeks followed by a combination of itraconazole and terbinafine. The patient gradually improved and was discharged home after 18 weeks of hospitalization.